Colloidal stability of milk: reinterpretation of alcohol test results by digital microscopy. Issue 1 (28th February 2022) - da Costa, Cláudio Humberto Ferreira; de Paula, Igor Lima; da Silva, Paulo Henrique Fonseca; Perrone, Ítalo Tuler; Stephani, Rodrigo; Cappa de Oliveira, Luiz Fernando
Abstract: In this research communication we propose a new approach by portable digital microscopy with a 200× objective to improve the visualization of microparticles of pasteurized milk submitted to the alcohol test. Not only did the method reduce the subjectivity of the readings, but also generated high resolution images of the microparticles, which allows the creation of a specific image pattern for each type of final product. In comparison to a control pasteurized milk treatment, the results confirmed the effect and the specificity of added salts (sodium citrate, disodium phosphate or their combination) on the stability of the milk to the alcohol test. Finally, the mixture of stabilizing salts of citrate/phosphate provided the highest degree of stability to pasteurized milk among the treatments studied.